2012
DOI: 10.1371/journal.pone.0049577
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ESE-3 Isoforms in Immunogenic and Tolerogenic Human Monocyte-Derived Dendritic Cells

Abstract: Dendritic cells (DC) are the only hematopoietic cells expressing the epithelial specific Ets transcription factor ESE-3. Here we analyzed presence and quantity of isoforms ESE-3a, ESE-3b and ESE-3j in various immunogenic and tolerogenic human monocyte-derived DC (moDC) and blood DC populations using quantitative real time PCR and immunoblot analyses. ESE-3a and ESE-3b were detectable in all moDC populations with ESE-3b being the main transcript. ESE-3b expression was upregulated in immunogenic moDC and downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 47 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…18, 21 EHF has been demonstrated to function as a potential tumor suppressor gene in prostate cancer and esophageal squamous cell carcinoma (ESCC), 19, 22, 23 and be frequently downregulated by promoter methylation. 22 On the other hand, it is overexpressed in ovarian and mammary cancers 24, 25, 26 and may be a predictive marker for poor survival in ovarian cancer. 24, 25 However, the roles of EHF in gastric tumorigenesis are not fully understood.…”
mentioning
confidence: 99%
“…18, 21 EHF has been demonstrated to function as a potential tumor suppressor gene in prostate cancer and esophageal squamous cell carcinoma (ESCC), 19, 22, 23 and be frequently downregulated by promoter methylation. 22 On the other hand, it is overexpressed in ovarian and mammary cancers 24, 25, 26 and may be a predictive marker for poor survival in ovarian cancer. 24, 25 However, the roles of EHF in gastric tumorigenesis are not fully understood.…”
mentioning
confidence: 99%
“…Functionally, Ehf is a transcriptional repressor of several genes regulated by MAPK signaling with a dependency on an Ets binding site (29). Recently, Ehf has been reported to be involved in the development of monocyte-derived dendritic cells (30)(31)(32).…”
mentioning
confidence: 99%
“…Surprisingly, stimulation of the cells with LPS had only little effect on ESE‐3 mRNA levels (2‐fold increase compared with immature cells), while previous studies showed a more pronounced effect . One possible explanation could be the variability between donors already observed previously, which might be caused by differences in TLR4 expression levels.…”
Section: Discussionmentioning
confidence: 69%
“…One possible explanation for the difference in ESE‐3b levels in tolerogenic DCs is the choice of method used to generate the cells. In our previous study, we used a combination of dexamethasone and vitamin‐D3, and 15‐Deoxy‐Δ12,14‐prostaglandin J2, respectively, to generate tolerogenic DCs , while in the present study, different PPAR‐ γ agonists were used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation